Relatedness, co-inquiring and imagination: mimetic images of recovery. Issue 3 (5th February 2018) - Gaggiotti, Hugo; Page, Margaret
Abstract : Purpose: The purpose of this paper is to explore the methodological challenges of developing a shared academic–student discourse of recovery with undergraduate students in their final year at a British business school. Design/methodology/approach: The authors reflect on the meaning of recovery and how it was negotiated and constructed by the relation established between students and academics, by analysing the visual- and text-based materials they produced and the discussions provoked by these materials using symmetric ethnology and content analysis. Findings: The main finding is that students tended to reflect on the real, particularly the social, by creating copies and replicas; the authors, as academics, engaged with this practice with ambivalence. The article concludes that this as an attempt to manage what is felt to be unmanageable, echoing what some authors consider to be a contemporary practice of social justification (Boltanski and Thévenot, 1991 ) and others consider to be a well-established cultural practice (Taussig, 1993 ). Research limitations/implications: The paper contributes to a better understanding of how relatedness and reflexive inquiry become essential for when teaching and that is linked with academics being able to be openly related with students and their situation; to a better understanding of recovery and how it can be co-constructed by academics and students through a share narrative; to a methodology for the analysis of text and images, and its appropriateness for the study of ways in which imagination of the future may be co-constructed; and to an understanding of mimetic objects, replicas and copies. Practical implications: The paper suggests that this approach could have practical implications when applying co-inquiry approaches of learning, the understanding of institutional and academic meaning of replication and relatedness in academic context of economic crisis. Originality/value: The authors conclude that academic relatedness and students–tutors engagement is constructed differently when re-considering replication as a way of learning. Preference for copying and pasting found texts and images, rather than creating, served as a way of managing the unknown and of constructing recovery through a process of "mimeting" (Campbell, 2005).